Penerapan ModelPembelajaran Osborn Untuk Meningkatkan Motivasi Belajar Seni Budaya Peserta Didik Smkn 2 Denpasar - I Wayan Sugama; Sindy Noviantari Subiartha; Dewa Ayu Dwita Respasti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Preparing Classroom Action Research (PTK) for the Classroom Therefore, this study aims to enhance motivation in learning arts and culture using the Osborn learning model. This type of research consists of two cycles and each cycle has four phases, viz. The subjects of this study are 32 students of class X AK 3 of SMK Negeri 2 Denpasar. This study was conducted from October to November 2023. The data analysis technique used was qualitative descriptive analysis using the Osborn learning model to examine the results of evaluating student presentations. by comparing learning outcomes with average completion scores. Research results show that the results of learning art and culture subjects in grade X AK 3 gradually increase from cycle 1 to cycle 2. This is clearly shown through the average increase obtained from the assessment results. present. The average score of the first semester class is 79, of which the highest score is 88 and the lowest score is 68. Meanwhile, in the second semester, the average score of the class is 87, the highest score is 93 and the lowest score is 82.